PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA AUGMENTED REALITY DENGAN MEDIA GAMBAR PADA TEMA 7 SUBTEMA 1 KELAS I MIN 3 KOTA MEDAN - Robenhart Tamba; Devi Fatia (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine the differences in the learning outcomes of junior high school students in Medan City for the 2019/2020 fiscal year 2019/2020 in the use of augmented reality media and image media on the sub-topic 7. 1) Living and non-living objects around us Level I MIN 3 This type of research is a quasi-experimental research. This research was conducted in MIN 3 Medan City. The population in this study were all 50 students of class 1 MIN 3 Medan. The sample includes 2 classes, namely class Ia with 25 students in experimental class II, and class Ib in experimental class I with 25 students. Data collection techniques in this study using observation and tests. The data analysis technique used normality, homogeneity, and hypothesis testing. The results of this study indicate that the average value of the Type I Experiment before treatment was 47.4, and after receiving augmented reality treatment the average value increased to 91.4. The average score of class II experimental students before treatment was 46.4, increasing to 78.6 after treatment. After knowing the mean, standard deviation, and variance of the various data, the significance level of the hypothesis results obtained using the t test is 0.05 to 7.009, and the t table is 1.676.Keywords: Augmented Reality Media, Media Images, Learning Outcomes